From Mythical to Mathematical Orientation: The "Cosmologicon" of the Hamburg Planetarium as a Branch of the Kulturwissenschaftliche Bibliothek Warburg - Fleckner, Uwe (ARJ – Art Research Journal: Revista de Pesquisa em Artes, 2022)
Aby Warburg’s “Collection of images on the history of astronomy and astrology”, opened 1930 in the Hamburg planetarium as a permanent exhibition, was the only completed project of his famous “image series” (the Atlas Mnemosyne included). Considered as a didactic tool for the citizens of Hamburg to understand the cultural history of astrology and astronomy, it assembled a wide range of reproductions of stars, constellations and superstitious as well as scientific images depicted in the arts from “primitive” peoples to the era of Dürer, Luther and Kepler. Warburg’s ambition was to create a reflexive distance (Denkraum) between men and the threatening phenomena experienced while looking into the sky: “The history of astronomy shows the manifold forms of human views of the world. Setting out from fear of demons and magic, humanity always has to travel afresh the path to the abstract logic of scientific observation”.